The Added Value Of Advertising Web Series In Indonesia On Youtube Content - Handriyotopo, Handriyotopo (Jurnal Ilmu Komunikasi, 2025)
This study aims to reveal the power of added value in web series advertising strategies through digital media, social media, YouTube, research object in the case SORE: wife from the future. This research method is qualitative with the perspective of making short film cinematography on web series advertisements as a strategy to introduce brands on YouTube social media. Analyzing with methods or 5 (five) important steps, namely; 1). Conduct research on serial web ad genre 2). How to view web series adv movie format 3). Analysis to find serial web ads can build value for brands. 4) How do Web series ads respond and follower counts? 5) Formulate YouTube's social media branding strategy. The findings of this study are the added value to branded web series that can be accessed by the public, shared quickly and commented on, and subscribed to YouTube content, resulting in economic added value if many subscribers are not found in advertisements on television. Costs in the cinematographic format of short films can be negotiated according to the choice of creative strategy to minimize production or not, is an option. With a talent strategy from many followers, it will accelerate the increase in the number of branded web series viewers through several broadcast episodes.